Experimental Investigation on Strength and Failure Characteristics of Cemented Paste Backfill - Zhang, Zhihong; Li, Jiacheng (Frontiers in Materials, 2021)
The strength characteristics of cemented paste backfill (CPB) in mining areas are the key control factors for the safety assessment of the overlying strata. A series of experiments about uniaxial compression and triaxial compression were carried out to study the influence of cement content of filling slurry, curing age, and curing temperature on strength characteristics of CPB specimens, furthermore, determine the failure mechanism and damage feature. The results show that: 1) the uniaxial compressive strength of CPB specimens increases with the increase of cement content and curing age. When the cement content is high, the uniaxial compressive strength increases sharply with the increase of curing age. 2) the cohesion of CPB specimens increases with the increase of cement content of filling slurry, curing age, and curing temperature. The cohesion of CPB specimens with curing age 7d and 14d increases linearly with the increase of cement content. At the later stage of curing age, the strength growth of high cement content backfill is significantly greater than that of low cement content. The internal friction angle of the filling only increases slightly with the increase of the filling cement content, curing age and curing temperature. 3) the shear strength of CPB specimens at 7d curing age increases significantly with the increase of confining pressure, while the shear strength at 14d and 28d curing age decreases slightly as the confining pressure increases. 4) with the increase of cement content in backfill, the brittleness increases significantly when the backfill damaged. The failure mode of CPB specimen changes from monoclinic section shear failure to X-type failure with the increase of curing age, and the failure process is divided into four stages: pore compaction, linear elastic deformation, plastic deformation and post-peak failure.